Application of the One Health approach to zoonotic diseases in Bhutan: A qualitative assessment of gaps and opportunities from key stakeholders’ perspectives - Bir Doj Rai; Tenzin Tenzin; Dorji Tshering; Narapati Dahal; Gizachew A. Tessema; Lin Fritschi; Sylvester Dodzi Nyadanu; Gavin Pereira (CABI One Health)
Abstract Background: The One Health (OH) approach integrates the human, animal, and environmental health sectors to address complex health challenges, including zoonotic diseases. Bhutan adopted the OH approach in 2013 and formalised it through the Bhutan One Health Strategic Plan in 2017. Despite significant progress, gaps in implementation persist, limiting the full operationalisation of OH initiatives. The underlying factors contributing to these gaps remain unclear. Aim: This study aimed to identify implementation gaps and opportunities for strengthening OH initiatives related to zoonotic disease prevention and control in Bhutan. Methods: A qualitative study was conducted using semi-structured interviews with 22 professionals from Bhutan’s key OH sectors, including public health, animal health, environmental agencies, and academia. Participants were purposively selected to capture diverse perspectives across national, regional and, district levels. Thematic analysis was conducted using a hybrid deductive-inductive approach. Data were managed in NVivo and reported according to the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Findings: The findings revealed gaps and opportunities across five themes: stakeholders, roles and, responsibilities; financial and personnel resources; communication and information, technical infrastructure, and governance. Key challenges include insufficient funding and human resources, an outdated strategic plan, a weak OH secretariat, fragmented reporting and communication systems, and inadequate research. Opportunities were identified in strengthening collaboration, integrating OH principles into educational curricula, enhancing research capacity, securing sustainable funding mechanisms, and revising the strategic plan to align with emerging needs and opportunities. Conclusions: Addressing the gaps requires a multifaceted approach, including updating the strategic plan, strengthening governance, securing sustainable funding, building human resource capacity, enhancing awareness, and improving communication. These efforts will enhance Bhutan’s OH implementation and strengthen zoonotic disease prevention and control. Furthermore, the findings provide valuable insights for other countries with similar contexts, supporting global efforts to operationalise OH and strengthen health security. One Health impact statement This study provides the first assessment of One Health implementation for zoonotic diseases control in Bhutan, offering valuable guidance for policymakers and professionals working at the human-animal-environment interface, to strengthen collaboration and policy development. Additionally, this research contributes to the global One Health agenda informing strategies in low- and middle-income countries facing comparable challenges. Bhutan has demonstrated the benefits of cross-sectoral cooperation in managing zoonotic diseases such as HPAI, rabies, anthrax and brucellosis. Notably, the country successfully controlled 17 HPAI outbreaks through One Health strategies, preventing human spillover – outcome unlikely through siloed efforts. This research makes a key contribution by integrating multisectoral and practitioner perspectives, drawing on the experiences of frontline health and veterinary workers to develop practical solutions that strengthen One Health in Bhutan, and beyond. Furthermore, this research demonstrates how authors from diverse sectors, countries and institutions collaborated to generate knowledge, reinforcing the interdisciplinary nature of One Health.